Revitalisasi Penerapan Qanun Nomor 6 Tahun 2014 tentang Hukum Jinayat di Kota Langsa Aceh - Junaidi, Junaidi; Bin Muhammadiah, Muhammad Rusdi; Muhazir, Muhazir (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This paper examines the problem of implementing the qanun jinayat in Langsa City Aceh Darussalam after the stipulation of Qanun Number 6 of 2016 concerning Jinayat Law, there are at least two groups of pros and cons to the enforcement of the Qanun Jinayat, the pro groups consider that the enforcement of the Jinayat Qanun is already good otherwise the contra group views that the enforcement of the Jinpu Law Qanun Jinayat is not optimal and seems to be selective so that many people underestimate the task of wilayatul hisbah and the Islamic Sharia Service. This type of research is non-doctrinal and the approach used is the sociological approach. Data collection techniques used are interviews and documentation. After conducting research it was found that enforcement of qanun jinayat in Langsa City Aceh Darussalam has not been implemented well. This is caused by several factors, namely: (1) the legal substance which shows that the contents of the qanun jinayat in Aceh are weak from the aspect of legal protection for women so that it is considered discrimination; (2) the legal structure relating to law enforcement is felt not to be firm against perpetrators of violations of the qanun jinayat; (3) the culture of legal awareness of the community is low so that jinayat violations still occur; (4) morality of law enforcement and fifth, legal support facilities.